Use of pinch concept to optimize the total water regeneration network - Parand, R; Yao, Hong Mei; Pareek, Vishnu; Tade, Moses (American Chemical Society, 2014)
In this study, an Extended Composite Table Algorithm is developed to target the minimum freshwater, regenerated water, and wastewater flow rates together with the minimum regeneration concentration and wastewater concentration for total water regeneration network. The approach is first demonstrated by assuming a fixed post-regeneration concentration. Considering that the post-regeneration concentration has the dominant influence on the total cost in the waterregeneration problem, this assumption is relaxed by allowing it to shift in a feasible region. A new method, Composite Matrix Algorithm, is proposed to find such a region and a maximum feasible post-regeneration concentration. By incrementally changing the post-regeneration concentration, the relationship between the key parameters in the total water regeneration network can beanalyzed quantitatively. Some graphical presentations are introduced to target total water regeneration problem when the removal ratio type regenerator is involved. Moreover, the effect of post-regeneration concentration to the total cost of the network is evaluated and discussed. To facilitate the implementation, MATLAB is used as a programing tool.